Середземномор’я – один з флористичних центрів інтродукції видів Quercus L. до Національного ботанічного саду імені М.М. Гришка НАН України - Doroshenko, O.K.; Oleshko, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – substantiation the degree of success of the genus Quercus L. species introduction based on the results of field and laboratory research and to determine the prospects for their practical use in our conditions. Material and methods. Search for introduced species of the genus Quercus is carried out and the list of species is made. Four of these species (Q. cerris L., Q. libani Oliv., Q. pubescens Willd. and Q. trojana Webb.) was borrowed for the collection of the arboretum in M.M. Gryshko National Botanical Garden of the NAS of Ukraine. Results. Phenological observations were carried out, the rhythm of growth and development of plants their response to extreme conditions in winter and summer were studied. Quality of seeds was studied in field and laboratory conditions. Based on eight years (2008–2015) of research and study of available literature sources we found the degree of success of the genus Quercus species introduction. Conclusions. The least successful is Q. trojana. Best of all feels plants of Q. pubescens.